Thumb Abscess In An Uncontrolled Diabetic Mellitus: A Brief Case Study (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Diabetes mellitus, a highly common metabolic condition in India and globally, presents a significant disease burden to the healthcare system. In addition to a myriad of potential complications, the high risk of infections is a particular area of concern. In an uncontrolled diabetic patient, even a small injury or trauma raises the possibility of developing a severe, fast-spreading infection. Infections in patients with diabetes are at the risk of progressing to an organ damage as well. Case Findings: We present a case report of a 58-year-old diabetic man, who was admitted to the surgical ward of a local tertiary care hospital. He presented with fever, thumb swelling and pain, along with erythema and pus discharge. These signs and symptoms were presented preceding an untreated rat bite during the last 10 days. Diagnosis, Interventions and Outcomes: Based on the history, physical examination and altered lab parameters, the clinician concluded it to be a case of abscess. After an initial pus collection, he was started on an antibiotic treatment; following which, an incision and drainage of the abscess was performed. An uncontrolled hyperglycemia was also managed by dose escalation and slight changes in the preexisting regimen. Timely antimicrobial and antihyperglycemic treatment, along with an efficient pus drainage proved to be beneficial in this case. Conclusion: Although the patient was vitally stable, it is likely for such conditions to take longer healing times, necessitating a focused care approach.